The effect of a community-based group intervention on chronic disease self-management in a vulnerable population - Korenhof, Sophie A.; Rouwet, Ellen V.; Elstgeest, Liset E. M.; Fierloos, Irene N.; Tan, Siok Swan; Pisano-Gonzalez, Marta M.; Boone, An L. D.; Pers, Yves-Marie; Pilotto, Alberto; López-Ventoso, Mónica; Diez Valcarce, Isabel; Zhang, Xuxi; et al. (Frontiers in Public Health, 2023)
Introduction Chronic non-communicable diseases (NCDs) are predominantly related to modifiable health behaviors, and account for 74% of global deaths currently. Behavior modification through self-management is a strategy to prevent NCDs. Chronic Disease Self-Management Programs (CDSMPs) have demonstrated improvements in health behaviors, health status and use of healthcare. Objective We evaluated the effects of a six-week CDSMP on self-efficacy, health behaviors, mental health, health-related quality of life (HR-QoL) and health responsibilities among vulnerable populations with chronic disease in Europe. Methods A prospective cohort study with a 6-month pre-post single-group design was conducted in five European countries. The intervention targeted adults with chronic conditions and a low socioeconomic status, as well as their caregivers. The intervention was a six-week community-based CDSMP in a group setting. Outcomes were measured, per self-report questionnaires at baseline and six-month follow-up: self-efficacy, health behaviors, mental health, HR-QoL, and health responsibilities. Results Of 1844 participants, 1248 (67.7%) completed follow-up and attended ≥4 sessions. For the chronic condition group, the following outcome measures at follow-up significantly improved compared to baseline (all P <0.002): self-efficacy (SEMCD-6 6.7 vs. 6.4), mental health (PHQ-8 6.3 vs. 7.0), HR-QoL (SF-12 PCS 42.3 vs. 40.2, SF-12 MCS 42.8 vs. 41.4), health utility (EQ-5D-5L 0.88 vs. 0.86), self-rated health (EQ-5D-5L 67.2 vs. 63.9), communication with healthcare providers (2.28 vs. 2.11), understanding information (3.10 vs. 3.02), number of doctor visits (3.61 vs. 4.97), Accident and Emergency department visits (0.25 vs. 0.48), total nights in a hospital (0.65 vs. 1.13) and perceived medical errors (19.6% vs. 28.7%). No significant changes were detected in dietary habits, physical activity, substance use, and sleep and fatigue. For caregivers without a chronic condition, only doctor visits significantly decreased (1.54 vs. 2.25, P < 0.001). Discussion This CDSMP was associated with improvement in self-efficacy, depression, HR-QoL and health responsibilities over six months in a diverse European population with a chronic condition. However, additional interventions targeting lifestyle risk factors are needed to improve health outcomes.